Service Quality at the Karampuang Village Office, Makassar City - Muh Asri H.R; Andi Aslinda; Andi Muhammad Rivai (Public Resource Innovation Management and Excellence, 2025)
This study aims to determine the quality of service at the Karampuang Village Office, Makassar City. To achieve this goal, the researchers used data collection techniques through documentation, observation, and interviews. The data obtained from the research results were processed using qualitative analysis to determine the quality of service at the Karampuang Village office, Makassar City. The results of the study indicate that the cause of the low quality of public services in Karampuang Village, Makassar City is caused by the indicators in the Tangible and Reliability dimensions that have not been implemented in accordance with service standards. The indicators that have not run according to service standards are (1) Tangible dimensions (physical evidence), namely the inconvenience of service places including non-functioning facilities.